THE ROLE OF USTADZ IN BUILDING CHILDRENS CONFIDENCE AT TPA AL-HAJI PALANGKA RAYA - Hamdanah Hamdanah; Surawan Surawan; Satria Nur Rizki (Proceeding International Seminar of Islamic Studies, 2022)
The phenomenon of lack of confidence in children affects the success of learning the Quran. So it is very difficult to understand the reading of the Quran. Roles are needed to be able to build self-confidence in children. TPA is a place where students are taught the Quran. Confidence is needed in this learning because it is at TPA that children are taught to be confident. Through existing programs, the role of Ustadz is needed in addition to transferring knowledge but also to give children an impact on confidence.This study was compiled by researchers using descriptive qualitative methods, with an analytical approach from the results of observations, interviews and documentation. From this method, the researchers tried to understand the role of the Ustadz at the TPA al-Haji in building self-confidence in children or students at the TPA al-Haji. In this case, the researcher describes systematically, factually, and accurately about the facts in the field. This study discusses the role of ustadz in building self-confidence in children. It can be seen in previous studies that many discuss in terms of understanding. In addition to understanding the self-confidence factor, it is also a factor in childrens success in reading and understanding the Quran.Keywords: Ustadzs Role, Child, self-confidence